COMPARISON OF REGENERATION RESULTS OF PREFABRICATED NERVE GRAFT, AUTOGENOUS NERVE GRAFT, AND VEIN GRAFT IN REPAIR OF NERVE DEFECTS - (:unkn) unknown (WILEY-BLACKWELL, 2009)
The purpose of this study was to evaluate the effectivity of prefabricated nerve grafts in the repairing nerve defect and to compare them with the autogenous nerve graft and vein graft. Four groups were created, each containing 10 rats. First, nerve prefabrication was carried out in groups I and II during 8 weeks. For this purpose, jugular vein graft was sutured to the epineural windows on the peroneal and tibial nerve at the right side in an end-to-side fashion. To create neurotrophic stimulus, partial incision was performed on the nerves in group I, and gene therapy was performed by plasmid injecting to the adjacent muscles in group II. At the end of the eighth week, prefabricated nerve grafts, jugular vein, and the axons passing through it were taken. Then, gap was created on the left peroneal nerve in all groups. Defect on the peroneal nerve was repaired by using the prefabricated nerve grafts in groups I and II, the autogenous nerve graft in group III, and the vein in group IV Assessment of nerve regeneration was performed by using electromyography. Morphological assessment was performed after follow-up period. According to electrophysiological and morphological results, the results of first three groups were similar. There was no statistically significant difference between three groups. Prefabricated nerve graft is as effective as autogenous nerve graft, and it can be used in the repair of nerve defects as autogenous nerve graft as an alternative. (c) 2008 Wiley-Liss, Inc. Microsurgery 29:138-143, 2009.
Keywords: TO-SIDE NEURORRHAPHY; POLYGLYCOLIC ACID CONDUITS; ENDOTHELIAL GROWTH-FACTOR; SILICONE CHAMBERS; SCHWANN-CELLS; GENE-THERAPY; RECONSTRUCTION; SURGERY; TRUNK; GAP